Immune responses to central nervous system directed adeno-associated virus gene therapy: Does direct CNS delivery make a difference? - Ashley L. Harkins; Prajakta P. Ambegaokar; Allison M. Keeler (Neurotherapeutics)
Adeno-associated virus (AAV) mediated gene therapy is a leading gene delivery platform with potential to transform the landscape of treatment for neurological disorders. While AAV is deemed non-immunogenic compared to other viral vectors, adverse immune reactions have been observed in the clinic, raising concerns. As the central nervous system (CNS) has a tightly regulated immune system, characterized by a degree of tolerance, it has been considered a unique target for AAV gene therapy. AAV vectors have shown promising results for the treatment of several CNS disorders including Spinal Muscular Atrophy, Giant Axonal Neuropathy, Amyotrophic Lateral Sclerosis, Tay Sachs Disease, Parkinson's Disease, and others, demonstrating safety and success. The Food and Drug Administration (FDA) approval of Zolgensma and European Medicines Agency (EMA) approval of Upstaza, for Spinal Muscular Atrophy (SMA) and Aromatic l-amino acid decarboxylase deficiency (AADC) respectively, represent this success, all while highlighting significant differences in immune responses to AAV, particularly with regards to therapeutic administration route. AAV therapies like Upstaza that are injected directly into the immune-specialized brain have been characterized by mild immune response profiles and minor adverse events, whereas therapies like Zolgensma that are injected systemically demonstrate more robust immune stimulation and off-target toxicities. Despite these contrasting parallels, these therapeutics and others in the clinic have demonstrated clinical benefit for patients, warranting further exploration of immune responses to CNS-directed AAV clinical trials. Thus, in this review, we discuss effects of different routes of AAV administration on eliciting local and peripheral immune responses specifically observed in CNS-targeted trials.